MANAJEMEN MAJELIS PENDIDIKAN DAERAH (MPD) DALAM MEMBERIKANPELAYANAN PENDIDIKAN DI KOTA SUBULUSSALAM PROVINSI ACEH - Refi Syaputra, Amiruddin Siahaan, Candra Wijaya (At-Tazakki: Jurnal Kajian Ilmu Pendidikan Islam dan Humaniora, 2018)
Abstract: This research uses qualitative naturalistic approach with field research type (field research).From some of the materials contained in this research, can be drawn some conclusions, among others: Ingeneral, the administrative education services of the secretariat and the response about all the educationalproblems of the Commissioners of the Regional Education Council (MPD) of Subulussalam Municipalityhave gone better than before. This is based on the results of observations of researchers, either from theobservation or direct interviews of the informants, and not least the informants from the external institutionitself. However, there are some indicators that have not been run in accordance with the wishes of thecommunity, among others: a) Not yet fulfilled or not perfect some commissions that have been mandatedby Qanun/Local Regulation of Subulussalam Municipality; b) There has not been found the working rulesof the commission in the Regional Education Council (MPD) of Subulussalam City, both conceptually andjuridically. Likewise, the completeness and supporting facilities in the field of administration entrusted tothe secretariat, until now there are still some indicators that have not been met include: a) The structure ofthe secretariat board has not been fully fulfilled; b) The Secretariat has three Subdivisions of which one ofthe publications and documentation looks not maximally empowered; c) The vision of the institutionalmission until now has not been updated; d) The most urgent office of the Regional Education Assembly(MPD) of Subulussalam City until now has not been realized.